Isotopic signatures of organic matter in the Upper Miocene-Pliocene Elbistan coal seam (Turkey): Insights from ?13C and ?15N variability - Kara, Hatice; Erturk, Mehmet Ali; Kalender, Leyla; Yalcin, Cihan; Turan, Mehmet Deniz; Sutcu, Emine Cicioglu (Pergamon-Elsevier Science Ltd, 2025)
This study examines the stable carbon (S13C) and nitrogen (S15N) isotope compositions of coal samples from the Upper Miocene-Pliocene (Neogene) Elbistan Basin, Turkey, to constrain the sources of organic matter and the depositional conditions of peat formation. A vertical sequence of samples collected from the K & imath;s,lakoy open-pit mine was analysed for total carbon and nitrogen contents, C/N ratios, and S13C-S15N values. The S13C values range from-28.09 %o to-16.99 %o, while S15N values vary between 1.97 %o and 4.99 %o. The carbon isotope data indicate a predominantly C3-type plant origin for the organic matter, with minor C4 contributions inferred from samples exhibiting enriched S13C signatures. Although some S13C enrichment may partly reflect microbial alteration of organic matter, the overall values remain consistent with a dominant C3 vegetation signal. Elevated S15N values suggest fluctuating redox conditions and microbial nitrogen cycling during peat accumulation. In comparison with other Turkish lignite basins and global coal deposits, the Elbistan samples display a broader isotopic range, reflecting a more complex paleoenvironmental evolution. The data suggest that the coal beds formed mainly in freshwater mire settings, where fluctuating water tables, variable redox conditions, and occasional inputs from C4 plants influenced peat accumulation. These results provide new insights into the paleobotanical and geochemical history of the basin and demonstrate the value of stable isotope analysis for reconstructing depositional environments in coal-bearing successions.
Keywords: Carbon isotope; Nitrogen isotope; Paleoenvironment; Organic matter source